2006
DOI: 10.4067/s0716-97602006000300014
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C isoform specificity of cholinergic potentiation of glucose-induced pulsatile 5-HT/ insulin release from mouse pancreatic islets

Abstract: Thymeleatoxin (TMX), an activator of Ca2+-sensitive protein kinase C (cPKC) isoforms, was used to assess the PKC isoform specificity of cholinergic potentiation of glucose (11 mM)-induced pulsatile 5-HT/insulin release (PIR) from single mouse pancreatic islets. TMX (100 nM) and carbachol (Cch, 50 μM) enhanced PIR 3-fold while reducing the underlying [Ca2+]i oscillations (duration and amplitude) by ~ 40-50%. Both effects were ablated by the specific PKC inhibitor bisindolylmaleimide and chronic TMX pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Findings showed that serotonin loaded into the beta cells localizes to the insulin secretory granules and is additionally co-released with it [26,27]. These authors demonstrated that there is little exocytotic activity of insulin + 5-HT at the basal glucose level, but increasing the sugar concentration results in increased insulin release from perfused beta cells.…”
Section: Peripheral Mechanismsmentioning
confidence: 74%
See 1 more Smart Citation
“…Findings showed that serotonin loaded into the beta cells localizes to the insulin secretory granules and is additionally co-released with it [26,27]. These authors demonstrated that there is little exocytotic activity of insulin + 5-HT at the basal glucose level, but increasing the sugar concentration results in increased insulin release from perfused beta cells.…”
Section: Peripheral Mechanismsmentioning
confidence: 74%
“…It is incorporated into the insulin granules of the former [22,23], at which level exerts a modulatory effect [24][25][26][27]. Conversely, 5-HT facilitates the secretion of glucagon from the alpha cells into the blood stream [21,[28][29][30].…”
Section: Peripheral Mechanismsmentioning
confidence: 99%
“…Raising the [Ca 2+ ] o from 2.56 to 12.8 mM evoked a pattern of oscillatory 5-HT release (leftmost portion of the trace in Fig. 5C) resembling that evoked by glucose under standard conditions [30]. Importantly, raising glucose concentration stepwise in the range 3-30 mM caused successive increments in the amount of 5-HT released per oscillation at the steady-state, as evidenced by an increase in both amplitude and duration of the individual oscillations (trace in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Release of pre-loaded 5-HT was monitored amperometrically using beveled glass-encased carbon fiber microelectrodes implanted in a single islet, as described [8,30]. Briefly, amperometric currents were measured using a pico-amperometer with the working electrode held at +0.55 V vs. Ag/AgCl.…”
Section: -Ht Releasementioning
confidence: 99%